2015
DOI: 10.1097/md.0000000000001032
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vascular Access Dysfunction and Subsequent Major Adverse Cardiovascular Events in Patients on Hemodialysis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“… 13 25 In the current study, Qa moderately and positively correlated with CI, which is in agreement with the findings of a previous study. Kuo et al 26 reported a significant association of vascular access dysfunction with subsequent major adverse CV events in chronic HD patients. These findings imply that lower Qa levels may be correlated with vascular access dysfunction, lower cardiac function and subsequent CV or cerebrovascular events.…”
Section: Discussionmentioning
confidence: 99%
“… 13 25 In the current study, Qa moderately and positively correlated with CI, which is in agreement with the findings of a previous study. Kuo et al 26 reported a significant association of vascular access dysfunction with subsequent major adverse CV events in chronic HD patients. These findings imply that lower Qa levels may be correlated with vascular access dysfunction, lower cardiac function and subsequent CV or cerebrovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial dysfunction, i.e., decreased NO production and reduced NO bioactivity, is considered a predictor for the development and progression of vascular diseases, 24,25 and a pivotal risk factor for cardiovascular events in patients with metabolic syndrome. 26 Impairment of vasorelaxation in response to NO occurs in the arteries of SHRSP.ZF rats with metabolic disorders. [20][21][22] The present study demonstrated that PNS enhances NO-dependent vasorelaxation in SHRSP.ZF rat arteries and that ginsenoside Rb 1 might be involved in this PNS-mediated effect.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that VA dysfunction was significantly associated with an increased risk of major adverse CV events (MACE) [40] . The investigators showed that the presence of VA dysfunction was associated with a higher risk of developing MACE in a dose-gradient pattern.…”
Section: Discussionmentioning
confidence: 99%